Radial Variation of Wood Axial Elements in Young Acacia Mangium Willd. and Serial Cross Sectioning of Shorea Leprosula Miq. - Honjo, Kiyoko (2002)
Wood quality, namely wood structure, physical and mechanical properties, and other qualities of woodworking, are greatly influenced by the proportion, type, morphology, arrangement, distribution, and specific gravity of xylem constituent cells. The present study was conducted to determine the radial variation pattern of wood axial elements in Acacia mangium Willd. In addition, the suitability of serial cross sectioning technique for wood fibre length determination in Shorea leprosula Miq. was also investigated. In the first part of the study, the radial variation pattern in the length of wood fibre and vessel element in Acacia mangium was investigated to reveal the difference in the pattern between dominant and suppressed trees. The correlation between the radial variation of wood fibre length and monthly climatic factors (average temperature and precipitation) in the early stage of tree growth was established.